City without Affordable Housing: Daily Experiences and Socio-Spatial Injustices in Greater Lomé (Togo) and Greater Nokoué (Bénin) - Bakam, Essodong; Samon, Sékdja Prosper; Anoumou, Kouassi Rodolphe; Aholou, Coffi Cyprien; Couchoro, Kodjovi Mawouli (Journal of Cultural Analysis and Social Change, 2025)
The dynamics of Greater Lomé (Togo) and Greater Nokoué (Benin) have led to a lack of affordable housing. This situation reflects the complex problem of access to housing for city dwellers. The aim of this article is to show how the lack of access to affordable housing is experienced by the populations of Greater Nokoué (Benin) and Greater Lomé (Togo). The research was based on a mixed approach combining household surveys (258 in Greater Lomé and 219 in Greater Nokoué), in-depth interviews (including 27 in Greater Lomé and 29 in Greater Nokoué). The results reveal a convergence of challenges in both cities, particularly the socio-economic conditions of households, real estate speculation, and limited government support for low-cost housing. The results also highlight contextual nuances, such as governance dynamics and socio-economic vulnerability, which influence respondents' access to housing. Respondent’s express feelings of marginalization, daily precariousness, and limited future prospects, which are symptomatic of social and spatial injustice.